A105 HIGH ADHERENCE TO SURVEILLANCE GUIDELINES IN IBD RESULTS IN LOW CRC AND DYSPLASIA RATES, WHILE RATES OF DYSPLASIA AND CANCER ARE LOW BEFORE THE SUGGESTED START OF SURVEILLANCE. RESULTS FROM A TERTIARY IBD CENTER. (15th March 2019) - Al Khoury, A; Singh, K; Kurti, Z; Gonczi, L; Reinglas, J; Verdon, C; Kohen, R; Bessissow, T; Afif, W; Wild, G; Seidman, E G; Bitton, A; et al.
Abstract: Background: Patients with Crohn's disease (CD) and ulcerative colitis (UC) are at increased risk for colorectal dysplasia (CRD) and cancer (CRC). Adherence to CRC surveillance guidelines is reportedly low internationally. Aims: To evaluate surveillance practices at the tertiary IBD Center of the McGill University Health Center (MUHC) and to determine CRD/CRC incidence. Methods: A representative IBD cohort with at least 8 years of disease duration (or with PSC) who visited the MUHC between July 1st -December 31st, 2016 were included. Adherence to surveillance guidelines was compared to modified 2010 BSG guidelines. Incidence of CRC, high-grade dysplasia (HGD), low-grade dysplasia (LGD), and colorectal adenomas (CRA) were calculated based on pathology. Results: 1356 CD and UC patients (disease duration: 12 (IQR:6–22) and 10 (IQR: 5–19) years) were identified. The surveillance cohort consisted of 689 patients (296 UC and 384 CD). Adherence to surveillance guidelines was 75.6/82.1% in UC/colonic CD. Adequate number of biopsies were taken in 53.7/54.2% of UC/colonic CD patients. Incidence of CRC/HGD in UC and CD with colonic involvement was 19.5/58.5 and 25.1/37.6 per 100, 000 patient-years, respectively. Incidence of dysplasia before 8 years of disease duration was low in both UC/CD (19.5 and 12.5/100, 000 patient-years) with no CRC detected. The CRA rate was 30/38% in UC/colonic CD. Conclusions: High adherence to surveillance guidelines and low CRC and dysplasia, but not CRA rates were found, suggesting that adhering to updated, stratified, surveillance recommendations may result in low advanced neoplasia rates. The incidence of dysplasia before the start of surveillance was low. Funding Agencies: None